Effect of Socioeconomic Status on the Linkage Between Suicidal Ideation and Suicide Attempts. Issue 5 (17th March 2016) - Kim, Jeong Lim; Kim, Ji Man; Choi, Young; Lee, Tae‐Hoon; Park, Eun‐Cheol
Abstract : Previous suicide attempts are a leading risk factor for completed suicide. To identify specific characteristics of those at high risk for attempts, we investigated associations with socioeconomic status (SES). Data from the 2013 Korean Community Health Survey (KCHS) included adults who reported suicidal ideation ( N = 220, 245). Attempts in the past 12 months were assessed. Associations of demographic, socioeconomic, and suicide‐related behavioral factors were analyzed using multiple logistic regression. Among those with suicidal ideation, 862 (3.9%) had attempted suicide. After stratification by age and gender, results showed that low education and unemployed young adult men and women had significantly higher rates of attempts. The lowest income level was associated with significantly higher rates of attempts in only young adult women. Among those with the lowest and highest income, the association between ideation and attempts was attenuated, whereas it was enhanced among other income groups.